Carbon molecular sieve membranes and methods of use thereof
By exposing the hollow fibers to the caustic solution and applying tension during the heat treatment, the problems of fiber sintering and linting are solved, achieving consistency in micropore size and improving gas separation efficiency.
Patent Information
- Application Number
- CN202380059396.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-18
- Filing Date
- 2023-08-17
- Publication Date
- 2025-03-25
AI Technical Summary
The prior art faces the problems of sintering and bleaching of hollow fibers when preparing carbon films for gas separation, resulting in inconsistent micropore sizes and affecting separation efficiency.
Consistency of micropore size is ensured by exposing the hollow fiber to a caustic solution and maintaining tension during heating and thermal degradation to prevent sintering and linting of the fibers.
The uniformity and mechanical strength of hollow fibers are improved, and the quality and efficiency of gas separation in the gas mixture are improved.
Smart Images

Figure CN119698322A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to U.S. Provisional Application Serial No. 63 / 399,017, filed on August 18, 2022, which is hereby incorporated by reference in its entirety. Technical Field
[0003] The present invention relates to the field of gas separation using carbon membranes. More specifically, the present invention relates to a method for producing a carbon membrane for separating gases, and a method for separating gases, and in particular hydrogen, from a gas mixture by passing the gas mixture through a carbon membrane of a polyvinylidene chloride copolymer hollow fiber. Background Art
[0004] Carbon molecular sieve (CMS) and CMS membranes are currently used to separate gases. CMS can be prepared from various resins that are pyrolyzed at different temperatures and / or under different conditions. Pyrolysis reduces the resin to carbon, but at least some porosity is maintained in the pyrolysis product in the form of micropores. Subsequently, the CMS formed in this way can be used in traditional gas separation equipment (such as packed beds, chromatographic columns, etc.) that adopts specific gas adsorption, wherein the size of the micropores determines which gas is adsorbed and which gas is not adsorbed in the gas mixture. According to, for example, traditional pressure swing adsorption methods or temperature swing adsorption methods, adsorption and desorption techniques can be used alternately for separation. CMS membranes are also used to separate gases by passing a gas mixture through a CMS membrane.
[0005] However, in the art, preparing CMS with micropores of the correct size for certain specific separations is a particular challenge. Since using CMS to perform separations assumes that the micropores are at least as large as or larger than the specific molecule that will enter the micropore, it is necessary to know the "size" of the specific molecule.
[0006] One material of choice for making CMS membranes is polyvinylidene chloride. Polyvinylidene chloride (PVDC) copolymers have previously been pyrolyzed to form carbon molecular sieves, but they tend to form larger pores. Lamond TG et al., "Research on the synthesis of SARAN-type carbons" Molecular sieve properties ( Molecular sieve properties of SARAN-type carbons”, Carbon (1965) 3, 59-63. The article describes the preparation of CMS from polyvinylidene chloride (PVDC) copolymers, which repel neopentane. molecules, but non-selectively adsorbs smaller molecules, such as CO2, butane, and isobutane in non-limiting examples. Given this, the authors of the article concluded that their CMS has Micropores.
[0007] Another example is disclosed in TACenteno et al., "Molecular sieve gas separation membranes based on poly(vinylidene chloride-co-vinyl chloride)", Carbon (2000) 38, 1067-1073. The article describes the use of the above materials to prepare a composite carbon membrane. The membrane is formed by a thin microporous carbon layer (thickness 0.8 micrometers, μm), which is obtained by pyrolysis of a polymer membrane and supported on a macroporous carbon substrate (pore size 1 μm; macroporosity 30%). Individual gas permeation experiments included helium (He), carbon dioxide (CO2), oxygen (O2), nitrogen (N2) and methane (CH4). For the O2 / N2 system, the selectivity is described as being particularly high, i.e., the selectivity at 25 degrees Celsius (0°C) is about 14. From this information it can be inferred that the micropore size falls within the range from the representative molecular diameter of O2 (3.46A) to the representative molecular diameter of N2 (3.64A). The CMS membrane was prepared by pre-treating the supported membrane at 200°C (the temperature at which the PVDC copolymer precursor melts prior to carbonization). The fact that melting is required means that the disclosed CMS structure cannot be prepared in an unsupported form.
[0008] In other studies (including, for example, Laredo GC, Meneses E., Castillo J., Marroquin JO, Jimeenez-Cruz F., "Adsorption equilibrium and kinetics of branched octane isomers on a polyvinylidene chloride-based carbon molecular sieve", Energy Fuels (2008) 22 (4) 2641-2648), CMS based on polyvinylidene chloride copolymers have been prepared, which exhibit relatively large micropore sizes and pore volumes, which are suitable for the separation of correspondingly large molecules, i.e., molecules with a molecular weight greater than 100 μm. Representative molecular diameters of those correspondingly larger molecules.
[0009] Recently, WO / 2016 / 003680 describes the formation of CMS from PVDC copolymers using a two-step pyrolysis at high temperatures of 800° C. to 1700° C. The average pore size of the formed CMS is to These CMS are described as being useful for the separation of: propylene (C3H6) and propane (C3H8); carbon dioxide (CO2) and nitrogen (N2); N2 and methane (CH4); ethylene (C2H4) and ethane (C2H6); and n-butane (C4H 10 ) and isobutane (C4H 10 ). Summary of the invention
[0010] Two problems associated with conventional methods for producing CMS membranes that consistently have pores of the correct size for certain specific separations are sintering and fluffing of the individual hollow fibers that make up the CMS membrane.
[0011] As used herein, "sintering" or "fusion" refers to a phenomenon in which individual hollow fibers constituting a CMS membrane fuse to each other by softening and melting during the manufacture of the individual hollow fibers. This may occur during the heating of the individual fibers, since it is known that substances such as PVDC soften when a temperature of 150°C or more is reached. Figure 1 As exemplified, the resulting fused fibers may have different pore sizes and may not be operable for gas separation by such fusion. Additionally, fused fibers may not produce uniform CMS membranes because the binder that may be used to bind the fibers together may not fully coat all of the outer surfaces of the fibers. Sintering of the fibers may also reduce the mechanical strength of the fibers, which may cause the fibers to pulverize during handling.
[0012] As used herein, "fuzzing" or "bending" refers to a phenomenon in which individual hollow fibers undergo bending during their manufacture. This phenomenon can make the appearance of a bundle of hollow fibers "fuzzy," or not look like a bundle of straight tubes. As described above, individual fibers are known to soften when temperatures of 150°C or above are reached. Therefore, when the structure is changed, the individual hollow fibers may warp or compress, thereby changing the shape of the fiber and its microporous structure. As Figure 2 As exemplified in Figure 1, the resulting fiber can experience significant bending along its length. As previously described, this can cause variations in micropore size within the fiber length, potentially leading to the capture of larger gas molecules than expected, or more significantly blocking certain pore spaces through curling, completely reducing the capture / sieving capacity in these areas. In addition, fluffing can cause fewer hollow fibers to be able to be packed together and lead to non-ideal fluid flow, thereby reducing the efficiency of the resulting CMS membrane.
[0013] Therefore, it is desirable to achieve CMS membranes and methods of making the same that do not encounter these fuzzing or sintering behaviors. The resulting CMS membranes will have consistent micropore sizes, allowing for separation of gases within gas mixtures based on representative molecular diameters. This can include gas mixtures encountered in syngas, gases produced in refineries, natural gas, and olefin cracker gas streams.
[0014] Therefore, a manufacturing method for producing CMS membranes made of hollow fibers without the aforementioned problems is discussed herein. The method of the present invention achieves this through two main features, whereby the hollow fibers are exposed to a caustic solution and they are held under tension as the hollow fibers are heated and thermally degraded. Exposure to the caustic solution generally prevents the individual hollow fibers from fusing, and the tension generally prevents the hollow fibers from fuzzing. This can result in improved separation quality of CMS membranes for gas mixtures without the fuzzing or sintering problems associated with other manufacturing methods.
[0015] According to one embodiment, a method for manufacturing a carbon molecular sieve (CMS) membrane includes: forming one or more hollow fibers, the one or more hollow fibers comprising a polyvinylidene chloride copolymer; exposing the one or more hollow fibers to a caustic solution, wherein the caustic solution comprises a strong base and a solvent; applying tension to opposite ends of the one or more hollow fibers to maintain the one or more hollow fibers in a straight shape; pretreating the one or more hollow fibers under the tension by heating at a first temperature of 120° C. to 200° C. using air, an inert gas, or a combination thereof; pyrolyzing the one or more hollow fibers at a second temperature of 500° C. to 1500° C. using an inert gas; and bundling the one or more hollow fibers to form the CMS membrane.
[0016] According to another embodiment, a method for separating a gas from a gas mixture comprises: forming a CMS membrane according to any embodiment described herein; and flowing the gas mixture through the CMS membrane to produce a permeate first stream having an increased concentration of first gas molecules and a second retentate stream having an increased concentration of second gas molecules, wherein the gas mixture comprises the first gas molecules and the second gas molecules, and the first gas molecules have a smaller representative molecular diameter than the second gas molecules.
[0017] Additional features and advantages of the embodiments described herein will be set forth in the following detailed description, and in part will become apparent to those skilled in the art from that description or may be recognized by practicing the described embodiments, including the detailed description and claims provided below. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The following detailed description of specific embodiments of the present disclosure may be best understood when read in conjunction with the accompanying drawings, in which:
[0019] Figure 1 is a scanning electron microscope (SEM) image of a polyvinylidene chloride (PVDC) copolymer hollow fiber with fusion (sintering);
[0020] Figure 2 is an image of a PVDC copolymer hollow fiber with fluff (bends);
[0021] Figure 3 is an image of a non-fluffed PVDC copolymer hollow fiber prepared according to an embodiment of the present invention;
[0022] Figure 4 is a SEM image of a PVDC copolymer hollow fiber without fusion prepared according to an embodiment of the present invention;
[0023] Figure 5 is an image of a carbon molecular sieve (CMS) membrane prepared according to embodiments herein;
[0024] Figure 6 is an image of a PVDC copolymer hollow fiber without fuzzing or fusing prepared according to embodiments herein; and
[0025] Figure 7 is an image of a hollow fiber test module according to an embodiment of the present invention. DETAILED DESCRIPTION
[0026] Embodiments described herein relate to methods of making carbon molecular sieve (CMS) membranes and methods of utilizing CMS membranes.
[0027] As used herein, "aqueous" may refer to a fluid that contains, produces, resembles, or has properties of water. As used herein, "non-aqueous" may refer to a fluid that does not contain water, does not produce water, does not resemble water, or does not have properties of water.
[0028] As used herein, "dehydrochlorination" may refer to an elimination reaction that removes hydrogen, chlorine, or a hydrogen halide from a substrate. For example, the dehydrochlorination of polyvinylidene chloride may involve a 1,2 elimination of an ion pair or a highly polarized four-center transition state. In another example, the dehydrochlorination includes a rearrangement of the chloroallyl structure to a cis-allyl configuration, which subsequently loses HCl via a six-center concerted process.
[0029] Additional features and advantages of the described embodiments will be set forth in the following detailed description, and in part will become apparent to those skilled in the art from the description or may be learned by practicing the described embodiments, including the following detailed description and the claims.
[0030] The gas permeation characteristics of a membrane (such as a CMS membrane described in further detail herein) can be determined by a gas permeation experiment. Two intrinsic properties are used to evaluate the separation performance of a membrane material: its "permeability" (a measure of the intrinsic productivity of the membrane); and its "selectivity" (P i ) (a measure of membrane separation efficiency). Usually expressed in Barrer The "permeability" is measured in units of i ) divided by the partial pressure difference between the upstream and downstream of the membrane (Δp i ) and multiplied by the thickness of the membrane (1) to calculate. In the embodiments herein, the thickness of the membrane can generally be expressed as the wall thickness of the hollow fiber (1) (OD-ID)* / 2:
[0031]
[0032] Another term, "permeability," is defined herein as the productivity of a CMS membrane or individual hollow fibers and is usually reported as a gas permeation unit (GPU). is measured by dividing the permeability by the effective membrane separation layer thickness:
[0033]
[0034] Finally, "selectivity" is defined in this article as the permeability of one gas through a membrane or the ratio of the permeability of another gas of the same nature. It is measured as a unitless ratio:
[0035]
[0036] As previously described, embodiments herein relate to methods for manufacturing carbon molecular sieve (CMS) membranes and processes utilizing CMS membranes. The method initially includes: forming or obtaining one or more hollow fibers. In an embodiment, one or more hollow fibers comprise polyvinylidene chloride copolymers. Subsequently, the method includes: exposing one or more hollow fibers to a caustic solution. Pretreating one or more hollow fibers by heating at a first temperature; and then pyrolyzing at a second temperature. Finally, one or more hollow fibers are bundled to form a CMS membrane.
[0037] In an embodiment, forming one or more hollow fibers may further include copolymerizing a polyvinylidene chloride copolymer with a comonomer to form a polyvinylidene chloride copolymer. The copolymerization method may include, but is not limited to, bulk polymerization, suspension polymerization, or emulsion polymerization. It is generally preferred that the copolymerization is carried out at a temperature (such as 10° C. to 120° C., 20° C. to 100° C., or 30° C. to 90° C.) to ensure that thermal degradation of all PVDC components in the PVDC component is avoided.
[0038] After copolymerization, the polyvinylidene chloride copolymer can be formed into one or more hollow fibers by any suitable method (such as those methods known in the art). For example, PVDC can be melt-extruded or solution-spun so that PVDC is formed into hollow fibers. Fibers can be produced by uniaxial stretching using known fiber processes for PVDC copolymers, and the fibers can be circular or shaped hollow fibers, or any other desired fiber morphology. It is also conceivable that precursor films and / or fibers can be coextruded with multiple PVDC copolymers and / or other polymers.
[0039] It should be noted that the fiber preparation method can optionally include stretching (such as the stretching of resin) to form melt extruded fiber. In a particular embodiment, this stretching can be particularly effective to induce faster crystallization and increase, and therefore particularly effective in improving the crystallite arrangement of one or more hollow fibers. Desirably, the draw ratio range is 1 to 8, such as 1 to 6, 1 to 4 and 2 to 4.
[0040] Generally, it is useful that one or more hollow fibers have a certain amount of crystallinity. In the present invention, the crystallinity is generally 25% to 75% of the resin or molded film, as measured by differential scanning calorimetry (DSC) according to ASTM D3418. In an embodiment, the level ranges from 30% to 55%, or the level ranges from 35% to 50%. Therefore, including comonomers generally helps to reduce the precursor crystallinity, to ensure the desired range, and also helps to reduce the melting temperature, thereby improving the processing properties of the resulting copolymer. Generally, compared with including monomers with smaller volumes, including monomers with larger volumes can tend to reduce the overall copolymer crystallinity to a greater extent. Therefore, for example, compared with, for example, methyl acrylate or ethyl acrylate, butyl acrylate will tend to reduce crystallinity to a greater extent, assuming that methyl acrylate or / and ethyl acrylate are based on the final copolymer composition with the same molar percentage (mol%) use.
[0041] The polyvinylidene chloride may have the general formula I, wherein n is an integer from 1 to 1000:
[0042]
[0043] As previously described, the polyvinylidene chloride copolymer can include at least one of vinylidene chloride and the following comonomers: vinyl monomers, vinyl chloride monomers, acrylate monomers, methacrylate monomers, styrene monomers, acrylonitrile, methacrylonitrile, itaconic acid and pyrolyzed chlorotrifluoroethylene. Based on the total weight of the copolymer, the polyvinylidene chloride copolymer can include at least 60% by weight or alternatively at least 70% by weight of vinylidene chloride. The polyvinylidene chloride copolymer can include up to about 97% by weight of vinylidene chloride, and therefore the polyvinylidene chloride copolymer can include at least 3% by weight of the comonomer previously stated in this paragraph. The polyvinylidene chloride copolymer can include 3% to 40% by weight, 3% to 30% by weight or 3% to 20% by weight of the comonomer. The polyvinylidene chloride copolymer can also include 3.5% to 15% by weight, 4% to 12% by weight, 7% to 28% by weight or 9% to 25% by weight of the comonomer.
[0044] One or more hollow fibers may also include additional additives. Additives may include but are not necessarily limited to epoxidized oil stabilizers, such as epoxidized soybean oil, epoxidized linseed oil, and diglycidyl ethers of bisphenol A. Also often used are liquid plasticizers, such as aliphatic and aromatic esters, including, for example, dibutyl sebacate, acetyl tributyl citrate, dioctyl phthalate, etc. and combinations thereof. Other commonly used additives may include lubricants, such as polyethylene wax, paraffin, oxidized polyethylene wax, and combinations thereof. Lubricants may optionally be included, and lubricants may include, for example, high-density polyethylene, acrylate copolymers, and silicone polymers and combinations thereof. Another group of additives that may be included is an acid scavenger, such as epoxy compounds, magnesium hydroxide, magnesium oxide, tetrasodium pyrophosphate, calcium phosphate, magnesium phosphate, DHT 4A (a synthetic hydrotalcite-like halogen scavenger available from Kyowa Chemical Industry), calcium oxide, calcium carbonate, and combinations thereof. Antioxidants may also be combined, such as phenolic resins. Any or all of these types of additives may be included in one or more hollow fibers.
[0045] In an embodiment, the total amount of all additives combined may be no more than 15% by weight of one or more hollow fibers, such as no more than 8% by weight or 3% by weight. However, in many applications, a combined amount of at least 2% by weight of all additives may be typical, so the range of use is 2% to 8% by weight or 2% to 3% by weight of one or more hollow fibers. Those skilled in the art will be aware of the use of such additives and their indications and contraindications without further guidance herein.
[0046] The one or more hollow fibers may each include an inner diameter and an outer diameter. The one or more hollow fibers may also include a length. In other words, the one or more hollow fibers may be considered a tube. This is for example Figure 1 and Figure 4 . The outer diameter of one or more hollow fibers can be 50 microns (micrometers) to 5000 microns. The outer diameter can also be any narrower range within the range of 50 microns to 5000 microns. For example, one or more hollow fibers can have an outer diameter of 50 microns to 100 microns, 100 microns to 1000 microns, 1000 microns to 2500 microns, 2500 microns to 4000 microns, 4000 microns to 5000 microns, or any combination of any endpoints of these ranges. One or more hollow fibers can also have a thickness between the inner diameter and the outer diameter. The thickness can be 10 microns to 100 microns. This is again, for example, Figure 1 and Figure 4 In Figure 1 In the case of a hollow fiber, each of the hollow fibers generally exhibits a thickness between the outer diameter and the inner diameter of the hollow space even when sintered. Similarly, Figure 4 Particularly in the left middle of the figure, the similar thickness between the outer diameter and the internal diameter of one or more hollow fibers is illustrated.For example, one or more hollow fibers can have an outer diameter of 50 microns and a thickness of 10 microns, so that the internal diameter is 30 microns.One or more hollow fibers can alternatively have an outer diameter of 5000 microns and a thickness of 100 microns, so that the internal diameter is 4800 microns.In embodiments, adjustable outer diameter and thickness to change the internal diameter, thus increase the possible flow velocity by the CMS membrane.Increasing the flow velocity by the CMS membrane can also increase the amount of the gas separated by the CMS membrane usually.
[0047] As previously described, the method also includes: exposing one or more hollow fibers to a caustic solution. The caustic solution may include a strong base and a solvent. The strong base may include lithium hydroxide, sodium hydroxide, potassium hydroxide, rubidium hydroxide, cesium hydroxide, calcium hydroxide, strontium hydroxide or a combination thereof. The strong base may also include an organic amine. In an embodiment, exposing one or more hollow fibers to a caustic solution may cause a cross-linking reaction to occur on the surface of a separate hollow fiber. Exposure to a caustic solution may also cause dehydrochlorination of the surface of a separate hollow fiber. The rate of the cross-linking reaction and the degree of the resulting surface cross-linking may depend on the strength and pH of the caustic solution used, and the amount of time that one or more hollow fibers maintain exposure to the caustic solution. When the hollow fiber is subsequently heated at a first temperature or a second temperature, the surface cross-linking of the separate hollow fiber may play a role in preventing the separate hollow fiber from softening face to face and melting into other hollow fibers. In other words, surface crosslinking due to exposure to caustic solutions can produce a crosslinked surface layer on the individual hollow fibers, thereby preventing softening and melting between the individual hollow fibers. This in turn can prevent one or more hollow fibers from fusing or sintering together, thereby ensuring a bundle of separate fibers and thereby improving the permeability and selectivity of the resulting CMS membrane. This is for example Figure 1 , Figure 3 and Figure 4 and are exemplified in the Examples herein. Figure 1 A bundle of hollow fibers is illustrated which has not been exposed to a caustic solution prior to heating. Figure 3 A bundle of hollow fibers is illustrated which has been exposed to a caustic solution prior to heating. Figure 4 The example of Figure 3 SEM image of a non-fused hollow fiber. Because the fibers are separated from each other, the epoxy resin is better able to wet and fill the space between the hollow fibers. Figure 3 and Figure 4 As shown, Figure 1 In contrast, exposure to the caustic solution resulted in reduced fusion of the individual hollow fibers.
[0048] It is contemplated that a weaker base (including but not limited to alanine, ammonia, methylamine, ammonium hydroxide, combinations thereof, or any other practical weaker base known to those skilled in the art) may be used in place of a strong base. However, it is further contemplated that if a weaker base is used, one or more hollow fibers will need to be maintained exposed to a longer period of time in the caustic solution to allow the caustic solution to fully crosslink the surface of one or more hollow fibers. In other words, the presence of a weaker base may reduce the crosslinking reaction rate on the surface of one or more hollow fibers.
[0049] The solvent may be an aqueous solution or a non-aqueous solution. The aqueous solution may be water. The water may be distilled water, deionized water or tap water. The non-aqueous solution may be tetrahydrofuran, an alcohol (such as but not limited to methanol), dimethylformamide, dimethyl sulfoxide or a combination thereof. It is contemplated that non-aqueous solutions may be preferred because they may better coat one or more hollow fibers with a strong base.
[0050] In embodiments, exposing caustic solution to one or more hollow fibers can include: keeping one or more hollow fibers completely immersed in caustic solution in a longer time period, or it can include: soaking one or more hollow fibers in caustic solution in a shorter time period. For example and in embodiments, one or more hollow fibers can be exposed to caustic solution for one second to ten seconds (shorter time period) or one minute to ten minutes (longer time period). After taking out one or more hollow fibers from caustic solution, caustic solution can also be partially retained on one or more hollow fibers. Caustic solution can continue to operate to crosslink the surface of a single hollow fiber until caustic solution is removed or the caustic element driving the crosslinking reaction is exhausted.
[0051] As previously mentioned, the method also includes: applying tension to one or more hollow fibers. In embodiments, tension can be 0.2MPa to 2MPa. Tension can also be 0.01MPa to 0.5MPa, 0.01MPa to 1MPa, 0.01MPa to 2MPa, 0.01MPa to 5MPa, 0.01MPa to 10MPa, 0.2MPa to 2.0MPa, 0.5MPa to 1MPa, 0.5MPa to 5MPa, 0.5MPa to 10MPa, 1MPa to 5MPa or 5MPa to 10MPa and any combination of the aforementioned range or any smaller range therein. Tension can be applied at the opposite end of one or more hollow fibers. In this way, tension can be applied at two open ends of one or more hollow fibers, which can operate to keep the relative shape of one or more hollow fibers as a rod or tubular structure, rather than a sheet. In embodiments, it is contemplated that stretching one or more hollow fibers into a sheet may render one or more hollow fibers unusable for their primary purpose, namely, preferentially separating two or more different types of gases. For example, stretching the hollow fibers into a sheet may block or otherwise disrupt the central hollow opening in one or more hollow fibers. The central hollow opening can be attributed to separation capabilities.
[0052] Applying tension to one or more hollow fibers may also include: an object of known weight is attached to one end of one or more hollow fibers. Applying tension may also include: an object of known weight is suspended on one or more hollow fibers, thereby applying the weight of the object as tension along the length of one or more hollow fibers. In an embodiment, one or more hollow fibers may be attached to an object of known weight by using a heat-resistant adhesive, tying one or more hollow fibers to an object of known weight or a combination thereof. In an embodiment, a system for applying tension to one or more hollow fibers may be configured to perform the same function in addition while bearing the temperature used in the pyrolysis step. This may include using a heat-resistant component, such as, but not limited to, using a heat-resistant adhesive.
[0053] In an embodiment, tension may be applied in such amounts so as to operate to maintain the length, current curvature (or lack of curvature), or both of one or more hollow fibers. In other words, tension may maintain the current curvature by keeping one or more hollow fibers straight. A tension less than or equal to the yield strength of the one or more hollow fibers may be applied. As used herein, "yield strength" is the tensile strength above which a material undergoes a specific amount of plastic deformation. Without being bound by any particular theory, it is contemplated that applying tension below or just below the yield strength of one or more hollow fibers may reduce the curvature that may be induced by later crosslinking and pyrolysis of the one or more hollow fibers. This is, for example, in Figure 2 and Figure 3 Example in. Figure 2 A bundle of hollow fibers that was not exposed to tension prior to heating is illustrated. The bundle of hollow fibers exhibited significant fuzzing and bending. This is consistent with Figure 3 In contrast, the figure shows another bundle of hollow fibers subjected to tension. This bundle of hollow fibers exhibits very little fuzzing or bending. As shown in the examples herein, when one or more hollow fibers are used in a CMS membrane to preferentially separate a gas mixture, the absence of bending can produce subsequent benefits, such as increased permeability or selectivity.
[0054] As previously described, the method also includes: pre-treating one or more hollow fibers under tension by heating with air, an inert gas, or both at a first temperature of 120°C to 200°C. In an embodiment, the pre-treatment of the one or more hollow fibers is used to stabilize or "lock" the copolymer structure before its pyrolysis / carbonization. In this step, the one or more hollow fibers are typically heated to a melting temperature below the PVDC so that the fibers are dehydrochlorinated to at least 10% of the extent. As used herein, the term "at least 10% dehydrochlorination" means that the hollow fibers have been pre-treated by removing hydrochloric acid to a point where the PVDC copolymer hollow fibers no longer melt and in fact begin to become non-fusible. It is recognized in the art that such changes in molecular dynamics begin to occur at a point of about 10% dehydrochlorination and are completed or maintained as the dehydrochlorination level increases beyond this point. In an embodiment, this "locking" of the copolymer structure can prevent further deformation or bending in the pyrolysis step after pre-treatment. Therefore, if the shape of the one or more hollow fibers is maintained by the tension applied in the pretreatment step, substantial fluffing of the one or more hollow fibers does not occur in the pyrolysis step.
[0055] The first temperature may also be any temperature range within 120°C to 200°C. For example, one or more hollow fibers may be heated at a first temperature of 120°C to 150°C, 120°C to 160°C, 120°C to 180°C, 150°C to 160°C, 150°C to 180°C, 150°C to 200°C, 160°C to 180°C, 160°C to 200°C, or 180°C to 200°C. In an embodiment, heating at any of these temperatures may crosslink the interior of one or more hollow fibers in addition to dehydrochlorination. As previously described, exposing one or more hollow fibers to a caustic solution prior to heating one or more hollow fibers may also prevent one or more hollow fibers from fusing to each other by producing a crosslinked surface layer on one or more hollow fibers while pretreating by heating at a first temperature. Pretreating one or more hollow fibers under tension may also include contacting one or more hollow fibers with air, an inert gas, or both. The contacting of the one or more hollow fibers with air or an inert gas can be carried out at a rate sufficient to purge pretreatment gas products (such as methane, hydrogen, carbon monoxide, and carbon dioxide) to prevent side reactions of the dehydrochlorinated gas products on the carbon surface. Contacting the one or more hollow fibers with air or an inert gas in the pretreatment step can occur at a rate of about 2000 mL / min.
[0056] In an embodiment, the pretreatment of one or more hollow fibers may also include: exposing one or more hollow fibers to a high energy radiation source, such as gamma rays, electron beams, ultraviolet light, or a combination thereof. The time may vary from 1 hour (hr) to 48 hr, preferably from 1 hr to 24 hr, and most preferably from 1 hr to 12 hr as required, to reach at least a 10% dehydrochlorination point, at which the copolymer begins to become infusible, i.e., no longer able to be melted. Depending on the pretreatment temperature and time, the dehydrochlorination degree may vary from 5% to 100%. If it is desired to have more visual confirmation of the onset of infusibility, additional confirmation of the dehydrochlorination percentage may be obtained, for example, by thermogravimetric analysis (TGA), using standard and well-known methods and equipment.
[0057] As previously described, the method also includes: pyrolyzing one or more hollow fibers with an inert gas at a second temperature of 500° C. to 1500° C. In an embodiment, pyrolysis can result in at least 90% by weight, more preferably at least 95% by weight, and most preferably at least 99% by weight of the copolymer being carbonized. As already noted above, pyrolysis is also referred to as "carbonization" because the result is that the copolymer is converted into a carbon-only or nearly carbon-only skeleton of its copolymer structure (that is, all or nearly all atoms except carbon are removed, but carbon-carbon bonds are substantially intact), and one or more hollow fibers can now be referred to as "carbon-containing". Pyrolysis can be performed using any means generally known to those skilled in the art.
[0058] The second temperature may also be any narrower temperature range within 500°C to 1500°C. For example, one or more hollow fibers may be pyrolyzed at a second temperature of 500°C to 650°C, 500°C to 1000°C, 500°C to 1250°C, 650°C to 1000°C, 650°C to 1250°C, 650°C to 1500°C, 1000°C to 1250°C, 1000°C to 1500°C, or 1250°C to 1500°C. In an embodiment, the inert gas may include carbon dioxide; nitrogen; any inert gas, including but not limited to argon; or a combination thereof. Pyrolyzing one or more hollow fibers at a second temperature may also include contacting the one or more hollow fibers with air, an inert gas, or both. Contacting the one or more hollow fibers with air or an inert gas may be performed at a rate sufficient to purge the pyrolysis gas products, thereby preventing side reactions of the dehydrochlorination gas products on the carbon surface. Contacting the one or more hollow fibers with the inert gas during the pyrolysis step may occur at a rate of about 300 mL / min.
[0059] As previously described, the method also includes: bundling one or more hollow fibers to form a CMS membrane. Bundling one or more hollow fibers may include: adding an adhesive to one or more hollow fibers, thereby binding the hollow fibers together. Adding an adhesive may also include: coating the outside of one or more hollow fibers with an adhesive, and contacting one or more hollow fibers coated with an adhesive with each other. In an embodiment, the adhesive may include an epoxy resin, a polyurethane, a silicone resin, an acrylic resin, or a combination thereof. The CMS membrane described herein may include 1,000 to 10,000 of one or more hollow fibers as a bundle. The CMS membrane may also have an area of 0.1 square meters to 10 square meters.
[0060] As described above, tension is applied to the one or more hollow fibers while they are being pretreated. However, tension can also be applied at any other step of the method. For example and in an embodiment, tension can be applied while exposing the one or more hollow fibers to a caustic solution simultaneously; while pyrolyzing the one or more hollow fibers simultaneously; or both. Tension can also be applied during the bundling step, the drying step discussed further below, the water bath step, or any other step.
[0061] The method may also include: drying one or more hollow fibers. For example and in an embodiment, the hollow fiber may be dried before or after pre-treating one or more hollow fibers. One or more hollow fibers may be dried by exposing one or more fibers to air, an inert gas, or both, below 120°C, by wiping and drying one or more hollow fibers, or both. Drying one or more hollow fibers may be operated to remove caustic solution from one or more hollow fibers, thereby terminating the surface cross-linking reaction of caustic solution and one or more hollow fibers. In an embodiment, one or more hollow fibers may also be subjected to at least one water bath before drying or pre-treatment. The water bath may be mainly composed of water. The water bath may remove additional caustic solution from one or more hollow fibers. This may be done by diluting the caustic solution in the case of an aqueous solvent, or by washing in the case of a non-aqueous solvent.
[0062] As previously discussed, CMS membranes may have a permeability, expressed as the permeability of gas flowing through the membrane layer thickness (individual hollow fiber wall thickness). However, CMS membranes may have different permeabilities for gases of different sizes. As previously discussed, the ratio of these different permeabilities may be expressed as the selectivity to a given gas. For example, CMS membranes may selectively separate different gases from each other. As discussed in further detail below, this may allow CMS membranes to act as preferential separators for gases of different sizes. For example and as shown in the embodiments of this article, CMS membranes may have propylene (C3H6) permeabilities of 2 to 12 GPUs and propane (C3H8) permeabilities of 0.05 to 0.8 GPUs. Therefore, CMS membranes may have propylene / propane selectivities of 12 to 54. This may allow CMS membranes to preferentially separate lighter propylene from heavier propane. It is conceivable that this behavior may extend to other olefin-alkane pairs, so that CMS membranes may preferentially separate olefins from alkanes.
[0063] In embodiments, the CMS membrane may also have a propylene (C3H6) permeability of 2 to 12 GPU, 2 to 11 GPU, 2 to 8 GPU, 2 to 5 GPU, 2 to 3 GPU, 2 to 2.5 GPU, or any range therein, such as 5 to 8 GPU or 2.5 to 11 GPU. The CMS membrane may also have a propane (C3H8) permeability of 0.05 to 0.8 GPU, 0.05 to 0.7 GPU, 0.05 to 0.5 GPU, 0.05 to 0.2 GPU, 0.05 to 0.1 GPU, or any range therein (e.g., 0.2 to 0.5 GPU or 0.05 to 7 GPU). The CMS membrane may also have a propylene / propane selectivity of any combination of the aforementioned propylene and propane ranges, such as any similar range between 16 to 25 or 12 to 54 therein.
[0064] As described above, embodiments of the present invention also relate to a method for separating a gas from a gas mixture. The gas mixture comprises a first gas molecule and a second gas molecule. The method comprises: forming a CMS membrane, and passing the gas mixture through the CMS membrane to produce a permeate first stream and a second retentate stream. The CMS membrane used in the method can be any CMS membrane previously discussed. The permeate first stream has a higher concentration of first gas molecules than the second retentate stream, which in turn has a higher concentration of second gas molecules than the permeate first stream. In this way, the CMS membrane used in the method can be operated to separate the first gas molecules and the second gas molecules from each other.
[0065] As previously described, determining the micropore / molecular size of a CMS membrane is important for determining the suitability of the CMS membrane for a particular separation. Different ways of measuring molecular size have been developed. A commonly used method is to measure the "kinetic diameter" of a given molecule. A reference that lists various of these kinetic diameters based on their use in zeolite applications is DW Breck, Zeolite Molecular Sieves: Structure, Chemistry and Use, John Wiley & Sons, Inc. (New York, NY 1974), 636 and these determinations are often used for non-zeolites, carbon molecular sieves known to have slit-shaped pores. In view of the foregoing and for the purposes of the present invention, the following kinetic diameters taken from the Breck reference cited above are used herein as representative molecular diameters of the following molecules: He H2 N2 CO2 CH4 C2H4 C3H8 i-C4H 10 SF6 (sulfur hexafluoride) and 8H 18 (Isooctane) However, because the reference table lacks a kinetic diameter for ethane and the kinetic diameter given therein for propylene is considered by at least some researchers to be inaccurate for the CMS material itself, for both materials the Lennard-Jones collision diameter is used in this paper rather than the Breck kinetic diameter. These Lennard-Jones collision diameters are and C3H6 See, e.g., Staudt-Bickel C., Koros W.J., "Olefin / paraffin gas separations with 61-DA-based polyimide membranes," J. Membr. Sci. (2000) 170(2), 205-214 for further discussion. The kinetic diameter and the Lennard-Jones collision diameter are collectively referred to as the "representative molecular diameter."
[0066] In an embodiment, the CMS membrane can have an average pore size greater than the representative molecular diameter of the second gas molecule. The average pore size of the CMS membrane can be measured by gas adsorption technology, using gas probe molecules of different sizes. The CMS membrane can have an average pore size greater than 3 angstroms, greater than 4 angstroms or greater than 5 angstroms. The CMS membrane can have an average pore size of up to about 15 angstroms. The CMS membrane can have an average pore size of 2 angstroms to 15 angstroms, 2 angstroms to 8 angstroms, 2 angstroms to 6 angstroms, 2 angstroms to 5 angstroms, 2 angstroms to 4 angstroms, 2 angstroms to 3 angstroms, 3 angstroms to 15 angstroms, 3 angstroms to 8 angstroms, 3 angstroms to 6 angstroms, 3 angstroms to 5 angstroms, 3 angstroms to 4 angstroms, 4 angstroms to 15 angstroms, 4 angstroms to 8 angstroms, 4 angstroms to 6 angstroms, 4 angstroms to 5 angstroms, 5 angstroms to 15 angstroms, 5 angstroms to 8 angstroms, 5 angstroms to 6 angstroms, 6 angstroms to 15 angstroms, 6 angstroms to 8 angstroms or an average pore size of 8 angstroms to 15 angstroms. The average pore size can be measured by gas adsorption.
[0067] In addition to the average micropore size, it is generally desirable in the art to optimize the total micropore volume, which can be measured via the Brunauer-Emmett-Teller (BET) method at liquid N2 temperatures. This can be further confirmed by helium (He) pycnometry and mercury (Hg) intrusion methods. For most separation applications, a total micropore volume of at least 0.10 mL / g, preferably at least 0.15 mL / g, and more preferably at least 0.20 mL / g at liquid N2 temperatures according to the BET method may be required to ensure commercially efficient adsorption of the desired gas.
[0068] In an embodiment, the gas mixture may include olefins, paraffins or both. The gas mixture may include at least two of carbon dioxide, nitrogen, carbon monoxide, methane, ethane, propane, ethylene, propylene, butane or butene. The first gas molecule and the second gas molecule may include any gas in the aforementioned gas, as long as the second gas molecule has a larger representative molecular diameter than the first gas molecule. For example, if the first gas molecule is propylene, the second gas molecule may be propane, butane or butene, i.e., any gas molecule with a larger representative molecular diameter than propylene. In an embodiment, the first gas molecule may include olefins, and the second gas molecule may include paraffins. The first gas molecule may also include at least one of hydrogen, ethylene, propylene or butene, and the second gas molecule may include at least one of carbon dioxide, nitrogen, carbon monoxide, methane, ethane, propane or butane.
[0069] Example
[0070] According to embodiments herein, the hollow fibers are formed by melt extrusion of PVDC copolymers of vinyl chloride. The properties of the hollow fibers are shown in Table 1 below. All chemicals used in the examples provided herein were purchased from Sigma Aldrich.
[0071] Table 1: Hollow fiber properties
[0072] characteristic value Outer diameter (micrometer) 164 Inner diameter (micrometer) 76 Wall thickness (micrometers) 44 Elastic modulus (MPa) 940 Elongation at break (%) 41
[0073] CMS membrane manufacturing
[0074] Subsequently, CMS membranes were formed from the hollow fibers according to embodiments herein. These CMS membranes were designated as Examples 1 to 3. The resulting membranes were used for permeation testing, as further described below.
[0075] Example 1 was formed by immersing 40 hollow fibers in a water-based caustic solution of 20 wt % NaOH (200 grams) for 5 minutes. The hollow fibers were then air dried overnight at room temperature (20°C). The hollow fibers were then subjected to a tension of 0.30 MPa by pulling a weight of 20 grams. The hollow fibers were then pretreated by heating at 140°C at a rate of 1°C / minute from room temperature using a 2 liter / minute air purge. The hollow fibers were then washed at least 6 times using an approximately 500 mL water bath to remove residual caustic solution. The hollow fibers were then dried at room temperature overnight. Visual observation of the pretreated hollow fibers did not show sintering or fuzzing of the hollow fibers, as previously discussed, because the caustic solution formed a cross-linked surface layer on the hollow fibers before pretreatment, and the tension prevented the fibers from bending during pretreatment.
[0076] The hollow fiber was then passed through an alumina tube with two inner holes (1 hollow fiber / alumina tube hole). The alumina tube was purchased from McMASTER-CARR (product #87175k71, with an outer diameter of 0.0094 inches, an inner diameter of 0.025 inches, and a length of 9 inches). The hollow fiber was then pyrolyzed in a furnace at a peak temperature of 600°C for two hours, with the temperature increasing at a rate of 3°C / minute from room temperature. An argon purge at a flow rate of 300 ml / min was also used to keep the furnace free of oxygen. The resulting hollow fiber was free of both sintering and fuzzing.
[0077] Example 2 was formed by immersing 40 hollow fibers in a non-aqueous caustic solution of 45 wt % KOH (200 g), tetrahydrofuran (100 g) and methanol (200 g) for 10 minutes. Subsequently, the hollow fibers were washed at least 6 times using an approximately 500 mL water bath to remove residual caustic. Subsequently, the hollow fibers were air dried overnight at room temperature (20° C.). Subsequently, the hollow fibers were subjected to a tension of 0.17 MPa by pulling a weight of 28 grams. Subsequently, the hollow fibers were pretreated for 24 hours by heating from room temperature at 1° C. / min with a 2 liter / min air purge. Subsequently, the hollow fibers were pretreated for another 12 hours by heating from 140° C. at a rate of 1° C. / min with a 2 liter / min air purge. Visual observation of the pretreated hollow fibers showed no sintering or fuzzing of the hollow fibers, as discussed previously, this was because the caustic solution formed an already cross-linked surface layer on the hollow fibers before pretreatment, and tension prevented the fibers from bending during pretreatment. Subsequently, the hollow fibers were pyrolyzed in the same manner as in Example 1. The resulting hollow fibers were free of both sintering and fuzzing.
[0078] Example 3 was formed by immersing 200 hollow fibers in the non-aqueous caustic solution of Example 2 of the present invention for 10 minutes. Subsequently, the hollow fibers were washed at least 6 times using an approximately 500 mL water bath to remove residual caustic. Subsequently, the hollow fibers were air dried overnight at room temperature (20° C.). Subsequently, the hollow fibers were subjected to a tension of 0.06 MPa by pulling a 20-gram weight. Subsequently, the hollow fibers were pretreated for 24 hours by heating from room temperature at 1° C. / minute at 140° C. using an air purge of 2 liters / minute. Subsequently, the hollow fibers were pretreated for another 12 hours by heating from 140° C. at a rate of 1° C. / minute at 170° C. using an air purge of 2 liters / minute. Visual observation of the pretreated hollow fibers did not show sintering or fuzzing of the hollow fibers, as previously discussed, because the caustic solution formed a cross-linked surface layer on the hollow fibers before pretreatment, and the tension prevented the fibers from bending during pretreatment. Subsequently, the hollow fibers were pyrolyzed in the same manner as in Example 1. The resulting hollow fibers were free of sintering and fluffing. Figure 6 exemplified.
[0079] Comparative CMS membrane manufacturing
[0080] Additional CMS membranes were also produced from hollow fibers for the purpose of comparison with the CMS membrane examples reported above. These CMS membranes were designated Comparative Examples 1 to 4. The resulting membranes were used for permeation testing as further described below.
[0081] Comparative Example 1 was formed by pre-treating 100 hollow fibers at 140°C with 2 liters / minute of air purge, heating at a rate of 1°C / minute from room temperature and maintaining for 24 hours. The hollow fibers of Comparative Example 2 were not subjected to any tension. Visual observation of the pre-treated hollow fibers showed significant sintering and fuzzing of the hollow fibers. Specifically, almost all of the hollow fibers were fused together. Due to the observed fusion and fuzzing, Comparative Example 1 was not further pyrolyzed or subjected to permeation testing.
[0082] Comparative Example 2 was formed by pre-treating 100 hollow fibers at 140°C with a 2 liter / minute air purge at a rate of 1°C / minute from room temperature and maintaining for 24 hours. The hollow fibers of Comparative Example 2 were subjected to tension by pulling a 20 gram weight. Visual observation of the pre-treated hollow fibers showed significant sintering of the hollow fibers. Specifically, similar to Comparative Example 1, almost all of the hollow fibers of Comparative Example 2 were fused together. Due to the observed fusion, Comparative Example 2 was not further pyrolyzed or subjected to permeation testing.
[0083] Comparative Example 3 was formed by pre-treating 100 hollow fibers by heating at 140°C at a rate of 1°C / min from room temperature using an air purge of 2 liters / min and maintaining for 24 hours. Each of the hollow fibers was separated in an alumina tube. No tension was applied to the hollow fibers. Subsequently, the hollow fibers were pyrolyzed according to Example 1 of the present invention. Visual observation of the pretreated hollow fibers showed that the hollow fibers were free of sintering and fuzzing. However, this was expected because each of the fibers did not contact each other and could fuse, and they were not allowed to bend significantly due to being constrained in the alumina tube.
[0084] However, even without sintering or fluffing, it is conceivable that the method of making hollow fibers of Comparative Example 3 is not suitable for the production of CMS membranes. Specifically, a CMS membrane as used in the method herein may include 1,000 to 10,000 individual hollow fibers as a bundle. In practical applications, this requires threading thousands of individual fibers into individual alumina tubes during the pretreatment stage to avoid fiber sintering. Especially when scaled up to industrial manufacturing scale, the separate costs of this method in terms of time and economy will make the resulting CMS membrane economically unfeasible.
[0085] According to the composition and method of Example 2 of the present invention, Comparative Example 4 is formed by immersing 200 hollow fibers in a caustic solution. Subsequently, the hollow fibers are also washed according to Example 2 of the present invention and then dried at room temperature overnight. Subsequently, each of these hollow fibers is individually inserted into an alumina tube and pretreated according to Example 1 of the present invention. No tension is applied to the hollow fibers. Subsequently, the hollow fibers are pyrolyzed according to Example 1 of the present invention. No sintering or fuzzing is observed in the fibers. However, like Comparative Example 3, this is expected because all the hollow fibers in the hollow fibers are not allowed to be significantly bent due to being individually constrained in the alumina tube. In addition, similar to Comparative Example 3, the method for manufacturing hollow fibers of Comparative Example 4 is not suitable for the production of CMS membranes. Specifically, Comparative Example 4 requires thousands of individual fibers to be inserted into individual alumina tubes in the pretreatment stage to avoid fiber fuzzing. As previously described, the individual costs of this method in terms of time and economy will make the resulting CMS membrane economically unfeasible, especially when scaled up to industrial manufacturing scale.
[0086] A summary of the results of making various hollow fibers is shown in Table 2 below.
[0087] Table 2: Summary of hollow fiber manufacturing
[0088]
[0089] Permeation testing of CMS membranes
[0090] Subsequently, any of the Examples and Comparative Examples were tested for gas permeability and gas selectivity. This was accomplished by building a custom annular permeation unit "module". Figure 7 As shown, the annular unit has a five inch outer diameter, a three inch inner diameter, four half-inch wide openings with 9 / 16 inch O-ring fittings in the wall, and a quarter inch thick cover with O-ring seals on both sides. The O-rings were provided by SAE / MS. Subsequently, ten hollow fibers according to the embodiment were inserted into the half-inch wide openings in the wall of the annular unit at approximately the 3 o'clock position and the 9 o'clock position. Teflon tape was used to make a cofferdam around the fiber bundle in the hole. Epoxy resin (Scotch Weld DP100) was used to fill the space around the hollow fiber holes and form a seal. This was for example made by Figure 4 Example. According to the previously described embodiment, a different hollow fiber is used for each module.
[0091] Subsequently, the module was used to perform a mixed gas permeation test at 35°C. A 50 / 50 propylene / propane gas mixture was initially introduced at 100 cm 3 / min to 200cm 3 / min. The gas mixture enters the module through a half-inch wide opening in the wall of the annular unit at about the 12 o'clock position, passes through the fiber bundle positioned across the center of the module, and exits the module as a retentate (resultant) stream through a half-inch wide opening in the wall of the annular unit at about the 6 o'clock position. The retentate stream is maintained at 52 psig (psi gauge pressure).
[0092] Then, use 20cm 3 / min to 50cm 3 The continuous argon purge of / min transports the permeate stream (the gas mixture trapped in the hollow fiber bundle) from the 9 o'clock position to the 3 o'clock position through the capillary of the hollow fiber to the area for gas chromatography (GC) analysis. The permeate flux is calculated using the argon purge flow rate and the permeate gas concentration measured by GC. As previously described, the permeability is calculated by using the permeate flux standardized by the total membrane area, which is the product of the exposed fiber length, the number of fibers, and the hollow fiber OD. As previously described, the unit of permeability is GPU, as measured by the following formula: Selectivity was determined by taking the ratio of propylene permeability divided by propane permeability. The results of the permeation testing are shown in Table 3 below. The lifetime of the examples reflects the number of days the examples spent in the nitrogen box between formation and testing in the module. Table 4 below shows the average results for hollow fiber based manufactured modules.
[0093] Table 3: Penetration test results
[0094]
[0095]
[0096] Table 4: Average penetration test results
[0097]
[0098] As shown in Tables 3 and 4 above, the examples demonstrate high selectivity for preferentially separating propylene from propane, indicating that they are useful in commercial applications for separating olefins from paraffins. Although the comparative examples also demonstrate selectivity for separating propylene and propane, the methods for making these examples are not suitable for commercial applications due to the complex nature of their manufacture. That is, each hollow fiber must be manually and individually threaded into an alumina tube to prevent sintering and fuzzing. This is a difficult solution to maintain when considering that a CMS membrane can include 1,000 to 10,000 individual fibers in operation, and that multiple CMS membranes can potentially be used in a manner close to commercial applications.
[0099] Furthermore, the above examples also tend to show that treating the fibers with KOH / non-aqueous solutions and pre-treating the hollow fibers at 140°C to 170°C produced hollow fibers with higher selectivity than all other examples. It is conceivable that the KOH / non-aqueous solution enhances these results because the non-aqueous solution can better coat all surfaces of the individual hollow fibers than an aqueous solution alone. It is further conceivable that the organic solvent can help to plasticize and swell the polymer chains of the pre-treated hollow fibers, thereby allowing the caustic to diffuse more easily into the fiber wall and achieve faster reaction times. Additionally, it is expected that the pre-treatment temperature of 140°C to 170°C also enhances these results by avoiding the peak melting temperature of the PVDC copolymer, which occurs above approximately 170°C. Therefore, operating just below 170°C can minimize local melting of the PVDC copolymer.
[0100] According to a first aspect, a method for manufacturing a carbon molecular sieve (CMS) membrane includes: forming one or more hollow fibers, the one or more hollow fibers comprising a polyvinylidene chloride copolymer; exposing the one or more hollow fibers to a caustic solution, wherein the caustic solution comprises a strong base and a solvent; applying tension to opposite ends of the one or more hollow fibers to maintain the one or more hollow fibers in a straight shape; pretreating the one or more hollow fibers under the tension by heating at a first temperature of 120°C to 200°C using air, an inert gas, or a combination thereof; pyrolyzing the one or more hollow fibers at a second temperature of 500°C to 1500°C using an inert gas; and bundling the one or more hollow fibers to form the CMS membrane.
[0101] Another aspect includes any of the preceding aspects, wherein the tension is applied to opposing ends of the one or more hollow fibers while exposing the one or more hollow fibers to the caustic solution, pyrolyzing the one or more hollow fibers, or both.
[0102] Another aspect includes any of the preceding aspects, wherein the tension is from 0.2 MPa to 2 MPa.
[0103] Another aspect includes any of the foregoing aspects, wherein the method further comprises: after exposing the one or more hollow fibers to the caustic solution, subjecting the one or more hollow fibers to at least one water bath to remove the caustic solution from the one or more hollow fibers; drying the one or more hollow fibers before pretreating the one or more hollow fibers under the tension; or both.
[0104] Another aspect includes any of the foregoing aspects, wherein pretreating the one or more hollow fibers under the tension further comprises: contacting the one or more hollow fibers with the air, the inert gas, or a combination thereof; pyrolyzing the one or more hollow fibers further comprises: contacting the one or more hollow fibers with the inert gas; and the inert gas comprises carbon dioxide, nitrogen, or both.
[0105] Another aspect includes any of the preceding aspects, wherein the polyvinylidene chloride copolymer comprises vinylidene chloride and at least one of the following comonomers: vinyl monomers, vinyl chloride monomers, acrylate monomers, methacrylate monomers, styrene monomers, acrylonitrile, methacrylonitrile, itaconic acid, and pyrolyzed chlorotrifluoroethylene.
[0106] Another aspect includes any of the foregoing aspects, wherein the strong base comprises lithium hydroxide, sodium hydroxide, potassium hydroxide, rubidium hydroxide, cesium hydroxide, calcium hydroxide, strontium hydroxide, or a combination thereof; and the solvent comprises an aqueous solution or a non-aqueous solution, the non-aqueous solution comprising tetrahydrofuran, alcohol, dimethylformamide, dimethyl sulfoxide, or a combination thereof.
[0107] Another aspect includes any of the preceding aspects, wherein each of the one or more hollow fibers comprises an inner diameter, an outer diameter, and a thickness between the inner diameter and the outer diameter; the outer diameter is 50 microns to 5000 microns; and the thickness is 10 microns to 100 microns.
[0108] Another aspect includes any of the preceding aspects, wherein the CMS membrane has a propylene permeability of 2 to 12 gas permeation units (GPUs); a propane permeability of 0.05 to 0.8 GPUs; and a propylene / propane selectivity of 12 to 54.
[0109] The tenth aspect includes any of the preceding aspects, and also includes a method for separating a gas from a gas mixture, the gas mixture comprising first gas molecules and second gas molecules, and wherein the method comprises: forming a CMS membrane according to any of the preceding aspects; and flowing the gas mixture through the CMS membrane to produce a permeate first stream having an increased concentration of the first gas molecules and a second retentate stream having an increased concentration of the second gas molecules, wherein the first gas molecules have a smaller representative molecular diameter than the second gas molecules.
[0110] An eleventh aspect includes the tenth aspect, wherein the CMS membrane has an average pore size greater than the representative molecular diameter of the second gas molecules as determined by gas adsorption using gas probe molecules of different sizes.
[0111] A twelfth aspect includes the tenth aspect or the eleventh aspect, wherein the CMS membrane has an average pore size greater than 3 angstroms.
[0112] A thirteenth aspect includes any one of the tenth to twelfth aspects, wherein the first gas molecules include olefins; and the second gas molecules include paraffins.
[0113] A fourteenth aspect includes any one of aspects ten to thirteen, wherein the CMS membrane has a propylene permeability of 2 to 12 gas permeation units (GPUs), a propane permeability of 0.05 to 0.8 GPUs, and a propylene / propane selectivity of 12 to 54; the first gas molecules include propylene; and the second gas molecules include propane.
[0114] The fifteenth aspect includes any one of the tenth to twelfth aspects, wherein the first gas molecules include at least one of hydrogen, ethylene, propylene or butene; and the second gas molecules include at least one of carbon dioxide, nitrogen, carbon monoxide, methane, ethane, propane or butane.
[0115] It should be noted that, unlike statements of intended use, statements in the present disclosure that a component of the present disclosure is "operable" or "sufficient" in a particular manner to embody a particular characteristic or function in a particular manner are structural statements. More specifically, references in the present disclosure to the manner in which a component is "operable" or "sufficient" refer to the existing physical condition of the component and, therefore, will be regarded as an explicit statement of the structural characteristics of the component.
[0116] The singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise.
[0117] Ranges are provided throughout the disclosure. It is anticipated that each discrete value encompassed by these ranges is also included. In addition, ranges formed by each discrete value encompassed by the explicitly disclosed ranges are also anticipated.
[0118] As used in this disclosure and the appended claims, the words "comprising," "having," and "including" and all grammatical variations thereof are each intended to have an open, non-limiting meaning that does not exclude additional elements or steps.
[0119] As used in this disclosure, terms such as "first" and "second" are arbitrarily designated and are intended only to distinguish between two or more instances or components. It should be understood that the words "first" and "second" have no other purpose and are not part of the component name or description, nor do they necessarily define the relative positioning, location, or order of the components. In addition, it should be understood that the use of the terms "first" and "second" alone does not require the existence of any "third" component, although such a possibility is contemplated within the scope of this disclosure.
[0120] The subject matter of the present disclosure has been described in detail and by reference to specific embodiments, it should be noted that the various details disclosed in the present disclosure should not be considered to imply that these details relate to elements that are essential parts of the various embodiments described in the present disclosure. In addition, it is apparent that modifications and changes can be made without departing from the scope of the present disclosure including but not limited to the embodiments defined in the appended claims.
Claims
1. A method for manufacturing a carbon molecular sieve (CMS) membrane, the method comprising: forming one or more hollow fibers, the one or more hollow fibers comprising a polyvinylidene chloride copolymer; exposing the one or more hollow fibers to a caustic solution, wherein the caustic solution comprises a strong base and a solvent; applying tension to opposite ends of the one or more hollow fibers to maintain the one or more hollow fibers in a straight shape; pretreating the one or more hollow fibers under the tension by heating at a first temperature of 120° C. to 200° C. with air, an inert gas, or a combination thereof; pyrolyzing the one or more hollow fibers at a second temperature of 500° C. to 1500° C. using an inert gas; and The one or more hollow fibers are bundled to form the CMS membrane.
2. The method of claim 1, wherein the tension is applied to opposing ends of the one or more hollow fibers while exposing the one or more hollow fibers to the caustic solution, pyrolyzing the one or more hollow fibers, or both.
3. A method according to any preceding claim, wherein the tension is from 0.2 MPa to 2 MPa.
4. The method according to any preceding claim, further comprising: after exposing the one or more hollow fibers to the caustic solution, subjecting the one or more hollow fibers to at least one water bath to remove the caustic solution from the one or more hollow fibers; drying the one or more hollow fibers prior to pretreating the one or more hollow fibers under the tension; or Both.
5. A method according to any preceding claim, wherein: Preconditioning the one or more hollow fibers under the tension further comprises: contacting the one or more hollow fibers with the air, the inert gas, or a combination thereof; Pyrolyzing the one or more hollow fibers further comprises: contacting the one or more hollow fibers with the inert gas; and The inert gas includes carbon dioxide, nitrogen, or both.
6. The method of any preceding claim, wherein the polyvinylidene chloride copolymer comprises vinylidene chloride and at least one of the following comonomers: vinyl monomers, vinyl chloride monomers, acrylate monomers, methacrylate monomers, styrene monomers, acrylonitrile, methacrylonitrile, itaconic acid, and pyrolyzed chlorotrifluoroethylene.
7. A method according to any preceding claim, wherein: The strong base includes lithium hydroxide, sodium hydroxide, potassium hydroxide, rubidium hydroxide, cesium hydroxide, calcium hydroxide, strontium hydroxide, an organic amine or a combination thereof; and The solvent includes an aqueous solution or a non-aqueous solution. The non-aqueous solution includes tetrahydrofuran, alcohol, dimethylformamide, dimethyl sulfoxide or a combination thereof.
8. A method according to any preceding claim, wherein: Each of the one or more hollow fibers comprises an inner diameter, an outer diameter, and a thickness between the inner diameter and the outer diameter; The outer diameter is 50 micrometers to 5000 micrometers; and The thickness is 10 micrometers to 100 micrometers.
9. A method according to any preceding claim, wherein the CMS membrane has: Propylene permeability from 2 to 12 gas permeation units (GPU); 0.05 to 0.8 GPU propane penetration; and Propylene / propane selectivity of 12 to 54.
10. A method for separating a gas from a gas mixture, the gas mixture comprising first gas molecules and second gas molecules, the method comprising: Forming a CMS membrane according to any preceding claim; as well as The gas mixture is flowed through the CMS membrane to produce a permeate first stream having an increased concentration of the first gas molecules and a second retentate stream having an increased concentration of the second gas molecules, wherein the first gas molecules have a smaller representative molecular diameter than the second gas molecules.
11. The method of claim 10, wherein the CMS membrane has an average pore size larger than the representative molecular diameter of the second gas molecules as determined by gas adsorption using gas probe molecules of different sizes.
12. The method of any one of claims 10 to 11, wherein the CMS membrane has an average pore size greater than 3 angstroms.
13. The method according to any one of claims 10 to 12, wherein: The first gas molecules consist of olefins; and The second gas molecules consist of chain alkanes.
14. The method according to any one of claims 10 to 13, wherein The CMS membrane has a propylene permeability of 2 to 12 gas permeation units (GPUs), a propane permeability of 0.05 to 0.8 GPUs, and a propylene / propane selectivity of 12 to 54; The first gas molecules consist of propylene; and The second gas molecules consist of propane.
15. The method according to any one of claims 10 to 12, wherein The first gas molecules include at least one of hydrogen, ethylene, propylene or butene; and The second gas molecules include at least one of carbon dioxide, nitrogen, carbon monoxide, methane, ethane, propane or butane.